2002
DOI: 10.2337/diacare.25.8.1432
|View full text |Cite
|
Sign up to set email alerts
|

Elevated C-Reactive Protein Associates With Early-Stage Carotid Atherosclerosis in Young Subjects With Type 1 Diabetes

Abstract: OBJECTIVE -To evaluate whether low-grade inflammation contributes to early-stage advanced carotid atherosclerosis in young subjects with type 1 diabetes.RESEARCH DESIGN AND METHODS -The mean and maximum (max) intimamedia thicknesses (IMT) of the carotid artery were assessed using ultrasound B-mode imaging in 55 patients with type 1 diabetes (22 men and 33 women, aged 22.1 Ϯ 3.6 years (Ϯ SD), duration of diabetes 14.2 Ϯ 5.7 years) and 75 age-matched healthy nondiabetic subjects (28 men and 47 women). High-sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 27 publications
5
77
1
2
Order By: Relevance
“…It has been thought that serum hs‐CRP level leads to the development of atherosclerosis5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16. Although various new pharmacological approaches have been introduced to reduce hs‐CRP levels17, 18, 19, 20, 21, 22, 23, 24, 25, 26, there are still many cardiovascular diseases all over the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been thought that serum hs‐CRP level leads to the development of atherosclerosis5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16. Although various new pharmacological approaches have been introduced to reduce hs‐CRP levels17, 18, 19, 20, 21, 22, 23, 24, 25, 26, there are still many cardiovascular diseases all over the world.…”
Section: Discussionmentioning
confidence: 99%
“…An increase of serum high‐sensitivity C‐reactive protein (hs‐CRP) level likely leads to the development of atherosclerosis. Indeed, it has been reported that hs‐CRP level is associated with carotid atherosclerosis in patients with type 2 diabetes mellitus5, 6, 7, 8, suggesting that hs‐CRP is a useful marker to predict an accelerated atherosclerotic process. It has also been shown that elevated hs‐CRP levels are associated with increased cardiovascular risk9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Four (40%) of the diabetics had a value of above 0.8 cm, which was a value of 2 standard deviations above the mean value obtained in a normal population of children in a study done by Hayaishi-Okano R et al [7]. Three The units of measurements were as follows: Age-years, HCY-umol/L, UACR-mg/g, TC and LDL-mmol/L, IMT-cm.…”
Section: Resultsmentioning
confidence: 99%
“…The computer program calculated the mean values of IMT from three separate images [26]. A value of > or equal to 0.8 cm was adjudged to be thickened; this was a value of 2 standard deviations above the mean value obtained in a normal population of children in a study done by Hayaishi-Okano R et al [7].…”
Section: Ultrasound Examinationmentioning
confidence: 99%
See 1 more Smart Citation